Enzymatic degumming of corn oil using phospholipase C from a selected strain of Pichia pastoris. (June 2019) - Sampaio, K.A.; Zyaykina, N.; Uitterhaegen, E.; De Greyt, W.; Verhé, R.; de Almeida Meirelles, A.J.; Stevens, C.V.
Abstract: Degumming is a necessary refining step for all crude vegetable oils. Purifine ® PLC is a new enzyme used for industrial oil degumming. In the present study, enzymatic degumming trials were performed on crude corn oil using a commercial phospholipase C enzyme Purifine ® PLC with the aim of determining its optimum process conditions. Enzymatic degumming applying 200 mg/kg of Purifine ® PLC during 120 min at 60 °C, and a pH of 5.7 using chemical conditioning, resulted in a residual phosphorus content of 27 mg/kg and an absolute diacylglycerol increase of 0.54 wt%. Compared to water degumming, enzymatic degumming with Purifine ® PLC provided a better degumming (67 mg/kg versus 27 mg/kg) and an increase in the diacylglycerol content. The pH adjustment of crude corn oil performed by means of a caustic pretreatment was not able to keep the pH at an optimal stable value due to the continuous release of acidic phosphate groups. Analysis of the composition of remaining phospholipids in the gums fraction showed that Purifine ® PLC could effectively convert phosphatidylcholine and phosphatidylethanolamine into diacylglycerols, whereas it could not convert phosphatidylinositol and phosphatidic acid. These results confirm that Purifine ® PLC degumming is a commercially feasible alternative to traditional degumming processes. Highlights: Optimum degumming conditions are 200 mg/kg of Purifine ® PLC during 120 min at 60 °C, and a pH of 5.7. Purifine ® PLC converted phosphatidylcholine and phosphatidylethanolamine into diacylglycerol. Purifine ® PLC provides an absolute diacylglycerol increase of 0.54 wt% in degummed corn oil.